PENINGKATAN KEMAMPUAN PEMAHAMAN MEMBACA DENGAN MODEL INTERAKTIF MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIKAL - Nia Ulfa Martha (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
This  study  used  an  experimental  approach  was  implemented  in  three  phases,  namely  Ability Test Reading Comprehension I, II, and III. The subject of this study is the student A morning class the  second semester of  Educational Studies Program Language and Literature Indonesia FKIP Unikal. This study variables in the form of interactive models of reading comprehension by answering questions and summarizing exercises. Collecting data on the KMP test I, II, and III  using  the  technique  in  the  form  of  deeds  and  nontes  tests.  Nontes  technique  used  is observation. The results showed an interactive model of reading comprehension by answering questions more effectively exercises used morning A class of students the second semester of Educational  Studies  Program  Language  and  Literature  Indonesia  FKIP  Unikal  to  improve reading  comprehension.  In  addition,  based  on  test  results  KMP  I,  II,  and  III  as  well  as observations  about  the  attitudes  of  students  during  the  learning  process  shows  that  the application  of  interactive  models  of  reading  comprehension  by  answering  questions  proved effective exercises improve student learning outcomes. Keywords: Improvement, reading comprehension, interactive model.